Verbalization of existential motif of death in a poetic picture of the world V. Svidzinskiy: semantic-syntactic aspect - Сметана, Ірина Ігорівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
In the article semantic-syntactic analysis of the representation in the competition of existential motif of death in the poetry of V. Svidzinskiy is presents. It is revealed that this motive is represented mainly by the structure of complex sentences. It has been investigated that for a figurative depiction of nature, devoid of life, the passage of time, the writer actively uses syntactic elements that complicate the sentences, but gives preference to homogeneous members, in particular predicate, and to isolated circumstances expressed by comparative turnovers. V. Svidzinskiy uses direct speech, dialog also, emotionally to select broadcasting of character, underline an utterance. For expressive expression of idea an author uses the different types of repetition, antithesis, parcelyaciyu and other stylistic receptions and figures.